The Influence of training and career development on the performance of functional employees of BMKG Region II, South Tangerang: PENGARUH PELATIHAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI FUNGSIONAL BMKG WILAYAH II TANGERANG SELATAN - Pratiwi, Deti; Erica, Denny; Budiastuti, Dewi Retno (Green Engineering Society, 2025)
Abstract. As an archipelagic country prone to disasters, Indonesia desperately needs timely and reliable meteorological, climatological, and geophysical (MKG) data. BMKG is a government agency primarily responsible for providing MKG data, including observation, data processing, analysis, forecasting, and early warning. he performance and competence of BMKG functional employees are crucial to ensure the accuracy and reliability of the information produced. Based on the research results With a calculated t value of 3.225 higher than the t table of 2.018 and a significance value of 0.002 which is smaller than 0.05, the results of this t test indicate that training (X1) has a significant effect on the performance of Functional employees, and career development (X2) also has a significant effect on employee performance, with a calculated t value of 2.372 higher than the t table of 2.018 and a significance value of 0.022 smaller than 0.05. Theoretically, this supports the hypothesis that good training and career development are proven to be positive and significantly increase employee productivity. It is concluded that increasing one's capacity through training and career development contributes to improving one's work results.. Abstrak. Sebagai negara kepulauan yang rawan bencana, Indonesia sangat membutuhkan data meteorologi, klimatologi, dan geofisika (MKG) yang tepat waktu dan dapat diandalkan. BMKG merupakan lembaga pemerintah yang bertanggung jawab utama dalam penyediaan data MKG, termasuk observasi, pengolahan data, analisis, prakiraan, dan peringatan dini. kinerja dan kompetensi pegawai fungsional BMKG sangat penting untuk menjamin keakuratan dan keandalan informasi yang dihasilkan. Berdasarkan hasil penelitian Dengan nilai t hitung sebesar 3,225 lebih tinggi dari t tabel sebesar 2,018 dan nilai signifikansi sebesar 0,002 yang lebih kecil dari 0,05, maka hasil uji t ini menunjukkan bahwa pelatihan (X1) berpengaruh signifikan terhadap kinerja pegawai Fungsional, dan pengembangan karir (X2) juga berpengaruh signifikan terhadap kinerja pegawai, dengan nilai t hitung sebesar 2,372 lebih tinggi dari t tabel sebesar 2,018 dan nilai signifikansi sebesar 0,022 lebih kecil dari 0,05. Secara teoritis, hal ini mendukung hipotesis bahwa pelatihan dan pengembangan karier yang baik dan terbukti positif serta signifikan meningkatkan produktivitas karyawan. Maka disimpulkan bahwa peningkatan kapasitas diri melalui pelatihan dan pengembangan karier berkontribusi pada peningkatan hasil kerja seseorang.